How stable are Australian farmers' climate change risk perceptions? New evidence of the feedback loop between risk perceptions and behaviour. (May 2021) - Wheeler, Sarah Ann; Nauges, Céline; Zuo, Alec
Highlights: Repeated surveys with the same 275 farmers over a five year period are analysed. Farmers became more accepting of climate change risk over time. Farmers facing a higher risk exposure were more concerned re climate change. A feedback loop between farmers' climate change concerns and behaviour was found. Farm behaviour that reduced risk exposure decreased climate change concerns. Abstract: The exact relationship between people's climate change attitudes and behaviour is a topic that engages policy-makers and researchers worldwide. Do climate change attitudes influence behaviour or is it possible that behaviour can change attitudes? This study uses a unique repeated survey dataset of 275 farmers (irrigators) in the southern Murray-Darling Basin from 2010–11 to 2015–16, to explore the dynamic relationship between climate change risk perceptions and farm adaptation behaviour. Farmers who had an increased risk exposure (expressed through higher debt, larger irrigated areas, greater share of permanent crops, and located in areas with higher temperatures and less rainfall) were more likely to agree climate change posed a risk. Whilst farmers became more accepting towards climate change over the time-period, a significant percentage of these attitudes were unstable. One reason suggested for this instability is the presence of a feedback loop between risk perceptions and behaviour. Namely, new evidence was found that farmers who agreed climate change was a risk in 2010–11, were more likely to undertake farm production decisions to reduce that risk (e.g. changing crop mix, reducing irrigated area and consequently selling water entitlements) – which had the impact of negatively feeding back and reducing their stated climate change risk perceptions in 2015–16. Conversely, farmers who were originally deniers were more likely to undertake somewhat riskier farm production decisions (e.g. increasing water utilisation rates and irrigation areas) – which consequently had the impact of positively increasing their climate change risk perceptions in 2015–16.